ANALISIS PRODUKTIVITAS PEGADAIAN SYARIAH BERDASARKAN UNSUR HUMAN CAPITAL (Studi Kasus Pada Pegadaian Syariah Kabupaten Aceh Jaya) - Rizwan, Rizwan; Nova, Nova (Fakultas Ekonomi Universitas Almuslim Bireuen, 2023)
Research in the form of a case study at one of the sharia pawnshops in Aceh Jaya district. In the form of survey research, descriptive and verification research types. It was found that: (1) the human capital factor based on individual capability was achieved at 78.3%. Individual motivation with an achievement level of 82%. The leadership aspect is still low at 74%. The organizational climate aspect is quite good at 82.3%, and the workgroup effectiveness aspect reaches 80.5%. The work productivity level of sharia pawnshops in Aceh Jaya is 80.67%. (2) Simultaneously, the relationship between human capital and work productivity is 0.898 with a large contribution of human capital from the elements of individual capability, individual motivation, leadership, the organizational climate, and workgroup effectiveness to work productivity, amounting to 80.7%.